ANALISIS RASIO AKTIVITAS, RASIO LEVERAGE, DAN RASIO LIKUIDITAS TERHADAP TINGKAT TERJADINYA FINANCIAL DISTRESS - Khasanah, Ainin; Astuti, Puji; Nurdiwaty, Diah (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to determine the effect of the fixed asset turnover ratio, debt ratio, and current ratio on the level of partial or simultaneous occurrence of financial distress in food and beverage sector manufacturing companies listed on the IDX. The analytical method used is multiple linear regression with SPSS version 23. The results of this study indicate that the ratio of fixed assets and current ratio partially has no effect on the occurrence of financial distress, the debt ratio partially has a significant effect on the occurrence of financial distress, and simultaneously the ratio of fixed assets, debt ratio, and current ratio affect the occurrence of financial distress. Previous research was conducted on the food and beverage sector listed on the IDX for the period 2013-2017, while this research was conducted on the food and beverage sector listed on the IDX for the period 2018-2021.